Use of advanced imaging in diagnosis of neurofibromatosis 1 - Eiti Singh; Khushboo Singh; Sunita Gupta; Mayank Shailat (Wolters Kluwer Medknow Publications, 2018)
Neurofibromatosis (NF) is a Mendelian disorder which is carried as an autosomal dominant trait. Two genetically distinct subtypes have been recognized, NF type 1 (NF1) and NF2. NF1 patients present with cutaneous, ocular, musculoskeletal, cardiovascular, gastrointestinal, neurologic, and dental findings but chiefly characterized by neurofibromas of central and peripheral nervous systems. Approximately 75%-80% of NF1 patients present with oral and radiographic manifestations, while 80% present with facial plexiform neurofibroma. This article aims to present a case report of NF1 diagnosed with the help of higher imaging. NF1 in a pediatric patient was diagnosed with classic findings of plexiform neurofibroma and sphenoid dysplasia diagnosed on cone-beam computed tomography (CT) and contrast-enhanced CT. Development of malignancies such as malignant peripheral nerve sheath tumors, optic gliomas, and leukemias is a major risk factor of NF1. Therefore, the use of imaging for early diagnosis of NF1 is critical.